Du surtravail émotionnel : quand l’organisation du travail oblige à sourire et bouillir - Fanny Darbus; Emilie Legrand (Perspectives Interdisciplinaires sur le Travail et la Santé)
Smile and chat even when you don't feel like it. This requirement, which typically applies to service workers, summarizes emotional labour. While this situation is the norm for these workers, we defend the idea that certain work organizations can produce emotional overwork. Based on a case study of a hairdressing salon operating on a no-appointment basis, we show that the work organization leads to a permanent flow of customers which, when combined with understaffing and the absence of a rest area, results in a particularly intense work load. In turn, this intensity engenders emotional overwork, which is particularly costly for health.